Recycled concrete material with anti-crack function and preparation process thereof

By pre -processing the regenerative coarse aggregate of the regenerative concrete, combined with the chemical reactions of corn core residues and sodium silicate, the problem of pores and cracks during the crushing process of regenerative concrete has significantly improved its crack resistance and overall performance Essence

CN119371171AInactive Publication Date: 2025-01-28YANCHENG INST OF IND TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411559153.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Recycled concrete is prone to pores and cracks during the crushing process, resulting in a lack of bonding with cement and prone to cracking, reducing compressive strength and limiting its promotion and application.

Method used

By pre -processing the regenerative coarse aggregate, the chemical reactions of corn core residues and sodium silicate are used to improve the performance of the aggregate surface, improve the adhesion with the remaining raw materials, and add crack fiber, nano -silicon dioxide and organic Silicine coupling agents and other ingredients enhance the crack resistance of concrete.

Benefits of technology

It improves the overall performance and cracking performance of regenerative concrete, enhances the density and strength of the aggregate, reduces the production of cracks, and improves the structural strength and durability of the concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005117408050000131
    Figure BDA0005117408050000131
  • Figure BDA0005117408050000141
    Figure BDA0005117408050000141
Patent Text Reader

Abstract

The invention discloses a recycled concrete material with an anti-crack function and a preparation process of the recycled concrete material with the anti-crack function. Comprising 300 to 400 parts of recycled coarse aggregate, 200 to 300 parts of recycled fine aggregate, 150 to 200 parts of cement, 50 to 80 parts of fly ash, 20 to 30 parts of silica fume, 3 to 5 parts of a water reducing agent, 150 to 200 parts of corncob residues, 0.1 to 0.2 part of sodium silicate, 5 to 10 parts of anti-crack fibers, 5 to 10 parts of nano-silica, 2 to 5 parts of an organic silane coupling agent, 8 to 12 parts of a rubber emulsion and 100 to 150 parts of water. Wherein the recycled coarse aggregate is prepared by pretreating corncob residues and sodium silicate according to a certain temperature and time, and then mixing the pretreated corncob residues and sodium silicate with the remaining raw materials. The recycled concrete material has good anti-crack function performance and high compressive strength, and the preparation process is simple, easy to operate and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, and in particular to a recycled concrete material with anti-crack function and a preparation process thereof. Background Art

[0002] With the development of the construction industry, the use of concrete is increasing, and a large amount of waste concrete is also generated. Recycled concrete, as a sustainable building material, is of great significance for the recycling of waste concrete. Recycled concrete refers to a green building material made by crushing, cleaning, grading, mixing with grading in a certain proportion, partially or completely replacing natural aggregates such as sand and gravel (mainly coarse aggregates), and then adding cement, water, etc. It can effectively solve the problems of low recycling rate of construction waste and resource depletion. However, waste concrete is subjected to large external forces during the crushing process, and there will be a large number of pores and cracks inside the recycled aggregate. The interface pores of recycled aggregate are more than those of natural aggregate, so the recycled aggregate is not tightly combined with cement. Recycled concrete using waste concrete as recycled aggregate is prone to cracking, which in turn reduces its compressive strength and limits the promotion and application of recycled concrete.

[0003] There are currently multiple solutions to the above problems. For example, the Chinese patent with publication number CN116477897A discloses a crack-resistant functional recycled concrete and its preparation method. A crack-resistant functional recycled concrete contains the following raw materials in parts by weight: 450-700 parts of recycled coarse aggregate, 400-550 parts of fine aggregate, 150-250 parts of cement, 80-120 parts of water, 50-75 parts of fly ash, 50-75 parts of slag powder, 5-10 parts of water reducer, 15-35 parts of tannic acid, and 10-25 parts of hydroxyapatite. Its preparation method is: mixing and stirring recycled coarse aggregate, fine aggregate, cement, water, fly ash, slag powder, water reducer, tannic acid and hydroxyapatite to obtain crack-resistant functional recycled concrete. The crack-resistant functional recycled concrete prepared by this scheme has good crack-resistant functional performance and high compressive strength.

[0004] Another example is a Chinese patent with publication number CN113735520A, which discloses a crack-resistant functional recycled concrete and a preparation method thereof. The recycled concrete comprises 450-750 parts of recycled coarse aggregate, 400-600 parts of recycled fine aggregate, 150-250 parts of cement, 80-120 parts of water, 50-80 parts of fly ash, 50-80 parts of slag powder, 15-20 parts of composite expansion agent, 10-20 parts of silane coupling agent, 5-10 parts of water reducer and 5-30 parts of fiber; the preparation method thereof is: mixing recycled coarse aggregate, recycled fine aggregate, cement, fly ash, slag powder and fiber according to the proportion and stirring them evenly to obtain a first mixture; adding the composite expansion agent to the first mixture and mixing them evenly to obtain a second mixture; adding water, silane coupling agent and water reducer to the second mixture and mixing them evenly to obtain the crack-resistant functional recycled concrete. The recycled concrete of the application can be used to reduce the porosity of recycled coarse aggregate and recycled fine aggregate, improve the compressive strength of the recycled concrete, and thus improve the crack resistance of the concrete.

[0005] Corncob is a lignocellulose raw material with extremely extensive resources in my country. At present, most of the xylose produced in my country's industry is extracted from corncob hydrolysate. In the process of xylose production, a waste rich in cellulose and lignin is produced - corncob residue, which is rich in cellulose and lignin. However, this resource has not been used in the current concrete industry.

[0006] Therefore, those skilled in the art are committed to developing a recycled concrete material and a preparation process thereof that can utilize corncob residues and has anti-cracking function. Summary of the invention

[0007] In view of the deficiencies in the prior art, the object of the present invention is to provide a recycled concrete material that can utilize corncob residues and has anti-cracking function and a preparation process thereof.

[0008] To achieve the above-mentioned invention object, the technical scheme adopted by the present invention includes: a recycled concrete material with anti-crack function, which includes, by weight, 300-400 parts of recycled coarse aggregate, 200-300 parts of recycled fine aggregate, 150-200 parts of cement, 50-80 parts of fly ash, 20-30 parts of silica fume, 3-5 parts of water reducer, 150-200 parts of corn cob residue, 0.1-0.2 parts of sodium silicate, 5-10 parts of anti-crack fiber, 5-10 parts of nano silicon dioxide, 2-5 parts of organic silane coupling agent, and 8-10 parts of rubber latex. 12 parts and 100-150 parts of water; wherein the recycled coarse aggregate is pretreated with corn cob residue and sodium silicate, and then mixed with the remaining raw materials, the pretreatment method steps are to continuously grind the corn cob residue into a fluid state, and then introduce it into the recycled coarse aggregate, gradually increase the temperature to 90-120°C, this process lasts for 11-30s, and then add sodium silicate with a concentration of 20-40mmol / L, adjust the temperature at 70-80°C, and maintain it for 20-30min to obtain the pretreated recycled coarse aggregate.

[0009] This pretreatment process can better crush and disperse the corn cob residue, so that the various components in the corn cob residue can be adsorbed on the recycled coarse aggregate at the first time; then it is further modified by sodium silicate. The sodium silicate solution will react with the calcium hydroxide on the surface of the recycled coarse aggregate to form calcium silicate gel, which fills the pores and cracks on the surface of the aggregate, improves the density and strength of the aggregate, and thus achieves the desired effect.

[0010] Furthermore, the weight ratio of cellulose, hemicellulose and lignin in the corncob residue is 20-30:10-20:40-50. Since lignin accounts for the majority of the corncob residue, the concrete structure made therefrom is relatively hard and has improved crack resistance.

[0011] Recycled coarse aggregate and recycled fine aggregate serve as the skeleton structure of concrete and provide basic strength support.

[0012] Cement acts as a cementitious material, binding the aggregates together.

[0013] Fly ash and silica fume, as mineral admixtures, can fill the gaps between aggregates, increase the density of concrete, reduce porosity, and thereby improve the strength and crack resistance of concrete.

[0014] Water reducers can reduce the amount of water used in concrete, reduce the water-cement ratio while ensuring the working performance of concrete, improve the strength and durability of concrete, and also help reduce the occurrence of cracks.

[0015] Anti-crack fibers form a three-dimensional network structure in concrete. When the concrete is subjected to external forces, the fibers can bear part of the stress and prevent the expansion of cracks, thereby significantly improving the concrete's anti-crack performance.

[0016] Nano-silica can fill the tiny pores in concrete and enhance the strength of concrete; organic silane coupling agent can improve the bonding force between the components; rubber latex has good flexibility and crack resistance. The three work synergistically to further improve the crack resistance of concrete.

[0017] Furthermore, the anti-cracking fiber is a combination of one or more of polypropylene fiber, basalt fiber, steel fiber and polyvinyl alcohol fiber.

[0018] Furthermore, the water reducer is one of a naphthalene-based water reducer, a polycarboxylic acid-based water reducer, an aminocarboxylic acid-based water reducer and a melamine-based water reducer.

[0019] Furthermore, the cement is slag cement and / or fly ash cement with low hydration heat. The present invention selects slag cement and / or fly ash cement with low hydration heat to reduce cracks caused by temperature changes in the hydration process of concrete.

[0020] Furthermore, the recycled coarse aggregate and recycled fine aggregate are obtained by crushing and screening waste concrete, and their particle sizes are 5-25 mm and 0.15-5 mm respectively.

[0021] Furthermore, calculated by weight, it includes 300 parts of recycled coarse aggregate, 300 parts of recycled fine aggregate, 200 parts of cement, 50 parts of fly ash, 30 parts of silica fume, 5 parts of water reducer, 200 parts of corn cob residue, 0.1 part of sodium silicate, 10 parts of anti-cracking fiber and 150 parts of water.

[0022] Furthermore, calculated by weight, it includes 400 parts of recycled coarse aggregate, 200 parts of recycled fine aggregate, 150 parts of cement, 80 parts of fly ash, 20 parts of silica fume, 3 parts of water reducer, 150 parts of corn cob residue, 0.2 parts of sodium silicate, 5 parts of anti-cracking fiber and 100 parts of water.

[0023] The present invention also provides a process for preparing a recycled concrete material with anti-crack function, comprising the following steps:

[0024] (1) The corncob residue is continuously ground into a fluid state, and then introduced into the recycled coarse aggregate, and the temperature is gradually increased to 90-120°C, and this process lasts for 11-30 seconds, and then sodium silicate with a concentration of 20-40 mmol / L is added, and the temperature is adjusted to 70-80°C, and maintained for 20-30 minutes to obtain the pretreated recycled coarse aggregate;

[0025] (2) Mixing the pretreated recycled coarse aggregate with the recycled fine aggregate, then adding 1 / 2 of the total amount of water, stirring and soaking for 40 to 60 seconds, adding cement, adding 1 / 4 of the total amount of water, and then continuing to stir and soak for 40 to 60 seconds to obtain pre-wetted aggregate;

[0026] (3) Add fly ash, silica fume and water reducing agent to the pre-wetted aggregate and stir evenly for 3 to 5 minutes;

[0027] (4) Add the anti-cracking fiber to the above mixture and continue to stir evenly for 2 to 3 minutes;

[0028] (5) Finally, add the remaining water and stir evenly to obtain a recycled concrete material with anti-crack function.

[0029] Furthermore, in step (1), the corn cob residue is continuously ground into a fluid state, and then introduced into the recycled coarse aggregate, and the temperature is gradually increased to 110°C. This process lasts for 30 seconds, and then sodium silicate with a concentration of 35 mmol / L is added, and the temperature is adjusted to 80°C and maintained for 30 minutes to obtain the pretreated recycled coarse aggregate.

[0030] Compared with the prior art, the advantages of the present invention include:

[0031] (1) Through the pretreatment of recycled coarse aggregate, corn cob residue is better combined with recycled coarse aggregate. During the pretreatment process, the high temperature and the action of sodium silicate cause the components in the corn cob residue to react chemically with the surface of the recycled coarse aggregate, improving the surface properties of the recycled coarse aggregate and increasing its bonding strength with the remaining raw materials, thereby helping to improve the overall performance and crack resistance of concrete.

[0032] (2) Corncob residues are mainly composed of cellulose, hemicellulose and lignin, and contain a small amount of nutrients such as protein and fat. Among them, cellulose and hemicellulose are the main carbohydrate components, and lignin is a complex organic polymer. Since the corncob residues selected in the present invention contain a large proportion of lignin, their structure is relatively hard, which improves the crack resistance.

[0033] (3) Corncob residue has a certain pore structure and adsorption properties, and is easy to combine with the remaining raw materials. Therefore, after pretreatment, a porous adsorption layer can be formed on the surface of the recycled coarse aggregate, which increases the contact area between the aggregate and the cement slurry and improves the bonding strength.

[0034] (3) The pore structure of corncob residue can also absorb part of the heat generated during cement hydration, reducing the internal temperature stress of concrete and reducing the occurrence of cracks.

[0035] (4) A small amount of hemicellulose in corncob residue can improve the rheological properties of cement, making the cement paste have better plasticity and water retention, which is beneficial to the construction and hardening process of cement.

[0036] (5) By adding anti-cracking fibers, the anti-cracking performance of recycled concrete is effectively improved, the occurrence of cracks is reduced, and the structural strength and durability of concrete are improved.

[0037] (6) Sodium silicate solution will react with calcium hydroxide on the surface of recycled coarse aggregate to form calcium silicate gel, which fills the pores and cracks on the surface of the aggregate and improves the density and strength of the aggregate.

[0038] (7) The preparation process of the present invention is simple, easy to operate, and suitable for large-scale production. DETAILED DESCRIPTION

[0039] In order to enable those skilled in the art to understand the characteristics and effects of the present application, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used herein have the common meanings understood by those skilled in the art for the present application. In case of conflict, the definitions in this specification shall prevail.

[0040] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present application in any way, that is, the content of the present application can be implemented without being limited by any specific theory or mechanism.

[0041] As used herein, "this application" means "the present invention" or "the present disclosure".

[0042] The use of "one", "an", "a kind" or similar expressions to describe the components and technical features described in this application is merely for the convenience of expression and to provide a general meaning to the scope of this application. Therefore, such description should be understood to include one or at least one, and the singular also includes the plural, unless it is obvious that it refers to another meaning.

[0043] In this document, "or its combination" means "or any combination thereof", and "any one", "any one" means "any one", "any one" or "any one".

[0044] As used herein, the terms "comprises," "including," "having," "containing," or any other similar terms are open-ended transitional phrases that are intended to cover non-exclusive inclusions. For example, a composition or article containing multiple elements is not limited to the elements listed herein, but may also include other elements that are not explicitly listed but are generally inherent to the composition or article. In addition, unless otherwise expressly stated, the term "or" refers to an inclusive "or" rather than an exclusive "or." For example, any of the following situations satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and both A and B are true (or exist). In addition, in this article, the terms "comprising", "including", "having", and "containing" should be interpreted as being specifically disclosed and simultaneously covering closed conjunctions such as "consisting of", "consisting of", and "the remainder is", as well as conjunctions such as "consisting essentially of", "mainly consisting of", "mainly consisting of", "basically containing", "essentially consisting of", "essentially consisting of", and "essentially containing".

[0045] In this article, all features or conditions such as numerical values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for simplicity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be deemed to have covered and specifically disclosed all possible sub-ranges and individual values ​​within the range (including integers and fractions), especially integer values. For example, the range description of "1.0 to 8.0" or "between 1.0 and 8.0" or "between 1.0 and 8.0" should be deemed to have specifically disclosed all sub-ranges such as 1.0 to 8.0, 1.0 to 7.0, 2.0 to 8.0, 2.0 to 6.0, 3.0 to 6.0, 4.0 to 8.0, 3.0 to 8.0, etc., and should be deemed to cover endpoint values, especially sub-ranges defined by integer values, and should be deemed to have specifically disclosed individual values ​​such as 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, etc. Unless otherwise indicated, the foregoing method of interpretation applies to all contents of the entire application, regardless of whether the scope is broad or not.

[0046] If the quantity, concentration or other numerical value or parameter is expressed as a range, a preferred range (or a better range) or a series of upper and lower limits, it should be understood that all ranges consisting of any pair of the upper limit or preferred value (or a better value) of the range and the lower limit or preferred value (or a better value) of the range have been specifically disclosed herein, regardless of whether these ranges are disclosed separately. In addition, if a numerical range is mentioned herein, unless otherwise specified, the range should include its endpoints and all integers and fractions within the range.

[0047] In this document, numerical values ​​should be understood to have the accuracy of the number of significant digits of the numerical value, provided that the purpose of the invention can be achieved. For example, the number 40.0 should be understood to cover the range of 39.50 to 40.49.

[0048] In this article, for the use of Markush groups or optional terms to describe the features or examples of the present application, those skilled in the art should understand that all subgroups or any individual elements in the Markush group or option list can also be used to describe the present application. For example, if X is described as "selected from the group consisting of X1, X2 and X3", it also means that the claim that X is X1 and the claim that X is X1 and / or X2 and / or X3 have been fully described. Furthermore, for the use of Markush groups or optional terms to describe the features or examples of the present application, those skilled in the art should understand that any combination of subgroups or individual members of all elements in the Markush group or option list can also be used to describe the present application. Accordingly, for example, if X is described as "selected from the group consisting of X1, X2 and X3", and Y is described as "selected from the group consisting of Y1, Y2 and Y3", it means that the claim that X is X1 and / or X2 and / or X3 and Y is Y1 and / or Y2 and / or Y3 has been fully described.

[0049] Unless otherwise specified, in this application, a compound refers to a chemical substance formed by two or more elements connected by chemical bonds, including small molecule compounds and polymer compounds, but not limited thereto. The interpretation of a compound in this article is not limited to a single chemical substance, but can also be interpreted as the same type of chemical substances with the same composition or the same properties.

[0050] If not otherwise specified, in this application, polymer refers to the product formed by monomer through polymerization reaction, often including many polymer aggregates, each polymer is formed by many simple structural units repeatedly connected by covalent bonds, and monomer is a compound of synthetic polymer. Polymer can include homopolymer, copolymer, prepolymer, etc., and is not limited to this. Homopolymer refers to a polymer polymerized by a monomer. Copolymer includes random copolymer (structure is such as -AABABBBAAABBA-), alternating copolymer (structure is such as -ABABABAB-), graft copolymer (structure is such as -AA(A-BBBB)AA(A-BBBB)AAA-) and block copolymer (structure is such as -AAAAA-BBBBBB-AAAAA-) etc. Prepolymer refers to a polymer with a molecular weight between a monomer and a final polymer with a lower molecular weight, and the prepolymer contains reactive functional groups that can further undergo polymerization reaction to obtain a product with a higher molecular weight that is fully cross-linked or hardened. Polymer certainly includes oligomers, and is not limited to this. Oligomers, also known as low polymers, are polymers composed of 2 to 20 repeating units, usually 2 to 5 repeating units.

[0051] Unless otherwise specified, the "resin" in this application is a customary name for a synthetic polymer, which may include monomers, polymers thereof, combinations of monomers, combinations of polymers thereof, or combinations of monomers and polymers thereof, etc., and is not limited thereto.

[0052] If not otherwise specified, in the present application, modified products include products after modification of reactive functional groups of each resin, products after prepolymerization of each resin with other resins, products after crosslinking of each resin with other resins, products after copolymerization of each resin with other resins, and the like.

[0053] If not otherwise specified, the unsaturated bonds described in the present application refer to reactive unsaturated bonds, such as but not limited to unsaturated double bonds that can undergo cross-linking reactions with other functional groups, such as but not limited to unsaturated carbon-carbon double bonds that can undergo cross-linking reactions with other functional groups.

[0054] The unsaturated carbon-carbon double bonds described in the present application preferably include, but are not limited to, vinyl, vinylbenzyl, (meth)acryloyl, allyl or a combination thereof. Vinyl should be interpreted to include vinyl and vinylidene. (Meth)acryloyl should be interpreted to include acryloyl and methacryloyl.

[0055] Unless otherwise specified, the hydrocarbon groups described in this application include, but are not limited to, alkyl, alkenyl or alkynyl, and include their various isomers when interpreted. For example, a C1-C6 divalent hydrocarbon group is interpreted to include a C1-C6 divalent straight-chain hydrocarbon group, a C2-C6 divalent branched hydrocarbon group or a C3-C6 divalent cyclic hydrocarbon group. For another example, a propyl group should be interpreted to include n-propyl and isopropyl.

[0056] Unless otherwise specified, in this application, parts by weight represent relative parts by weight in a composition, which may be any weight unit, such as but not limited to kilograms, kilograms, grams, pounds, etc. For example, 100 parts by weight of polyphenylene ether resin may represent 100 kilograms of polyphenylene ether resin or 100 pounds of polyphenylene ether resin.

[0057] It should be understood that the features disclosed in the various embodiments herein may be arbitrarily combined to form the technical solution of the present application, as long as there is no contradiction in the combination of these features.

[0058] The present application will be described below with specific implementations and examples. It should be understood that these specific implementations and examples are merely illustrative and are not intended to limit the scope of the present application and its use.

[0059] Unless otherwise stated, the methods, reagents and conditions used in the following preparation examples, comparative examples and examples are conventional methods, reagents and conditions in the art.

[0060] The raw materials of each component below are purchased from the market, and their specific sources or characteristics are as follows:

[0061] Recycled coarse aggregate, recycled fine aggregate: Xuchang Jinke Resources Recycling Co., Ltd.;

[0062] Cement: BBMG PSA 32.5 Portland slag cement, Tangshan Jidong Cement Co., Ltd.;

[0063] Naphthalene-based water reducer: Jinan Mingguan Chemical Co., Ltd.

[0064] Polycarboxylic acid high-performance water reducer: Jining Sanshi Biotechnology Co., Ltd.;

[0065] Fly ash: Shijiazhuang Bennuo Mineral Products Co., Ltd.;

[0066] Silica fume: Shandong Boken Silicon Materials Co., Ltd.;

[0067] Glass fiber: Huimin County Taili Chemical Fiber Products Co., Ltd.;

[0068] Basalt fiber: Huimin County Taili Chemical Fiber Products Co., Ltd.

[0069] Steel fiber: Huimin County Taili Chemical Fiber Products Co., Ltd.;

[0070] Polyvinyl alcohol fiber: Huimin County Taili Chemical Fiber Products Co., Ltd.

[0071] Polypropylene fiber: Huimin County Taili Chemical Fiber Products Co., Ltd.

[0072] Example 1

[0073] In terms of weight, the recycled concrete materials of this embodiment include 300 parts of recycled coarse aggregate, 300 parts of recycled fine aggregate, 200 parts of cement, 50 parts of fly ash, 30 parts of silica fume, 5 parts of polycarboxylic acid water reducer, 200 parts of corn cob residue, 0.1 parts of sodium silicate, 10 parts of polypropylene fiber, 10 parts of nano-silicon dioxide, 5 parts of organic silane coupling agent, 12 parts of rubber latex and 150 parts of water, wherein the particle size of the recycled coarse aggregate is 10-25 mm, and the particle size of the recycled fine aggregate is 0.15-2 mm.

[0074] The preparation process is as follows:

[0075] (1) The corncob residue was continuously ground into a fluid state and then introduced into the recycled coarse aggregate. The temperature was gradually increased to 110°C. This process lasted for 30 seconds. Then, sodium silicate with a concentration of 35 mmol / L was added and the temperature was adjusted to 80°C. The temperature was maintained for 30 minutes to obtain the pretreated recycled coarse aggregate.

[0076] (2) The pretreated recycled coarse aggregate is mixed with the recycled fine aggregate, and then 1 / 2 of the total amount of water (i.e., 75 parts) is added, and after stirring and soaking for 60 seconds, cement is added, and 1 / 4 of the total amount of water (i.e., 37.5 parts) is added, and then stirring and soaking is continued for 60 seconds to obtain pre-wetted aggregate.

[0077] (3) Add fly ash, silica fume, water reducer, nano-silica, organic silane coupling agent and rubber latex to the pre-wetted aggregate and stir evenly for 5 minutes.

[0078] (4) Add anti-cracking fiber to the above mixture, such as polypropylene fiber, and continue to stir evenly for 3 minutes.

[0079] (5) Finally, the remaining water (i.e. 37.5 parts) was added and stirred evenly to obtain a recycled concrete material with anti-crack function.

[0080] Example 2

[0081] In terms of weight, the recycled concrete materials of this embodiment include 400 parts of recycled coarse aggregate, 200 parts of recycled fine aggregate, 150 parts of cement, 80 parts of fly ash, 20 parts of silica fume, 3 parts of aminocarboxylic acid water reducer, 150 parts of corn cob residue, 0.2 parts of sodium silicate, 5 parts of basalt fiber, 5 parts of nano-silica, 3 parts of organic silane coupling agent, 8 parts of rubber latex and 100 parts of water, wherein the particle size of the recycled coarse aggregate is 10-25 mm, and the particle size of the recycled fine aggregate is 0.15-2 mm.

[0082] The preparation process is as follows:

[0083] (1) The corncob residue was continuously ground into a fluid state and then introduced into the recycled coarse aggregate. The temperature was gradually raised to 90°C. This process lasted for 11 seconds. Then, sodium silicate with a concentration of 20 mmol / L was added and the temperature was adjusted to 70°C. The temperature was maintained for 20 minutes to obtain the pretreated recycled coarse aggregate.

[0084] (2) The pretreated recycled coarse aggregate is mixed with the recycled fine aggregate, and then 1 / 2 of the total amount of water (i.e., 50 parts) is added, and after stirring and soaking for 40 seconds, cement is added, and 1 / 4 of the total amount of water (i.e., 25 parts) is added, and then stirring and soaking is continued for 40 seconds to obtain pre-wetted aggregate.

[0085] (3) Add fly ash, silica fume, water reducer, nano-silica, organosilane coupling agent and rubber latex to the pre-wetted aggregate. If an aminocarboxylic acid water reducer is used, stir evenly for 3 minutes.

[0086] (4) Add anti-cracking fiber to the above mixture, such as basalt fiber, and continue to stir evenly for 2 minutes.

[0087] (5) Finally, the remaining water (i.e. 25 parts) is added and stirred evenly to obtain a recycled concrete material with anti-crack function.

[0088] Example 3

[0089] By weight, the recycled concrete materials include 350 parts of recycled coarse aggregate, 250 parts of recycled fine aggregate, 180 parts of cement, 65 parts of fly ash, 25 parts of silica fume, 4 parts of polycarboxylic acid water reducer, 180 parts of corn cob residue, 0.15 parts of sodium silicate, 8 parts of anti-cracking fiber (polypropylene fiber and basalt fiber mixed in a ratio of 1:1), 8 parts of nano-silicon dioxide, 2 parts of organic silane coupling agent, 8 parts of rubber latex and 130 parts of water. The particle size of the recycled coarse aggregate is 5-15 mm, and the particle size of the recycled fine aggregate is 2-5 mm.

[0090] The preparation process is as follows:

[0091] (1) The corn cob residue was continuously ground into a fluid state and then introduced into the recycled coarse aggregate. The temperature was gradually increased to 100°C. This process lasted for 20 seconds. Then, sodium silicate with a concentration of 30 mmol / L was added and the temperature was adjusted to 75°C. The temperature was maintained for 25 minutes to obtain the pretreated recycled coarse aggregate.

[0092] (2) The pretreated recycled coarse aggregate is mixed with the recycled fine aggregate, and then 1 / 2 of the total amount of water (i.e. 65 parts) is added, stirred and soaked for 50 seconds, and then cement is added, and 1 / 4 of the total amount of water is added, and stirred and soaked for 50 seconds to obtain pre-wetted aggregate.

[0093] (3) Add fly ash, silica fume, water reducer, nano-silica, organic silane coupling agent and rubber latex to the pre-wetted aggregate and stir evenly for 4 minutes.

[0094] (4) Add polypropylene fiber and basalt fiber in a ratio of 1:1 into the above mixture and continue stirring evenly for 2.5 minutes.

[0095] (5) Finally, the remaining water (i.e. 32.5 parts) was added and stirred evenly to obtain a recycled concrete material with anti-crack function.

[0096] Example 4

[0097] By weight, the recycled concrete materials include 320 parts of recycled coarse aggregate, 280 parts of recycled fine aggregate, 160 parts of cement, 70 parts of fly ash, 22 parts of silica fume, 3.5 parts of aminocarboxylic acid water reducer, 160 parts of corncob residue, 0.12 parts of sodium silicate, 6 parts of steel fiber, 9 parts of nano-silicon dioxide, 4 parts of organic silane coupling agent, 9 parts of rubber latex and 120 parts of water. The particle size of the recycled coarse aggregate is 5-15 mm, and the particle size of the recycled fine aggregate is 2-5 mm.

[0098] The preparation process is as follows:

[0099] (1) The corn cob residue was continuously ground into a fluid state and then introduced into the recycled coarse aggregate. The temperature was gradually increased to 100°C. This process lasted for 20 seconds. Then, sodium silicate with a concentration of 40 mmol / L was added and the temperature was adjusted to 75°C. The temperature was maintained for 25 minutes to obtain the pretreated recycled coarse aggregate.

[0100] (2) The pretreated recycled coarse aggregate is mixed with the recycled fine aggregate, and then 1 / 2 of the total amount of water (i.e. 60 parts) is added, stirred and soaked for 50 seconds, and then cement is added, and 1 / 4 of the total amount of water is added, and stirred and soaked for 50 seconds to obtain pre-wetted aggregate.

[0101] (3) Add fly ash, silica fume, water reducer, nano-silica, organic silane coupling agent and rubber latex to the pre-wetted aggregate and stir evenly for 4 minutes.

[0102] (4) Add the steel fiber into the above mixture and continue stirring for 2 minutes.

[0103] (5) Finally, the remaining water (i.e. 30 parts) is added and stirred evenly to obtain a recycled concrete material with anti-crack function.

[0104] Example 5

[0105] By weight, the recycled concrete materials include 380 parts of recycled coarse aggregate, 220 parts of recycled fine aggregate, 190 parts of cement, 55 parts of fly ash, 28 parts of silica fume, 4.5 parts of naphthalene water reducer, 170 parts of corncob residue, 0.18 parts of sodium silicate, 7 parts of polyvinyl alcohol fiber, 10 parts of nano silicon dioxide, 3 parts of organic silane coupling agent, 11 parts of rubber latex and 140 parts of water. The particle size of the recycled coarse aggregate is 10-25 mm, and the particle size of the recycled fine aggregate is 2-5 mm.

[0106] The preparation process is as follows:

[0107] (1) The corn cob residue was continuously ground into a fluid state and then introduced into the recycled coarse aggregate. The temperature was gradually increased to 100°C. This process lasted for 20 seconds. Then, sodium silicate with a concentration of 30 mmol / L was added and the temperature was adjusted to 75°C. The temperature was maintained for 25 minutes to obtain the pretreated recycled coarse aggregate.

[0108] (2) The pretreated recycled coarse aggregate is mixed with the recycled fine aggregate, and then 1 / 2 of the total amount of water (i.e. 70 parts) is added, and after stirring and soaking for 55 seconds, cement is added, and 1 / 4 of the total amount of water (i.e. 35 parts) is added, and then stirring and soaking is continued for 55 seconds to obtain pre-wetted aggregate.

[0109] (3) Add fly ash, silica fume, water reducer, nano-silica, organic silane coupling agent and rubber latex to the pre-wetted aggregate. If a naphthalene-based water reducer is used, stir evenly for 4.5 minutes.

[0110] (4) Add polyvinyl alcohol fiber to the above mixture and continue stirring evenly for 2.5 minutes.

[0111] (5) Finally, the remaining water (i.e. 35 parts) is added and stirred evenly to obtain a recycled concrete material with anti-crack function.

[0112] Comparative Example 1

[0113] The amounts of corncob residue and sodium silicate and the pretreatment step of the recycled coarse aggregate in Example 1 were removed, and the remaining raw material amounts and operating steps remained unchanged.

[0114] The preparation process is as follows:

[0115] (1) Recycled coarse aggregate and recycled fine aggregate are mixed, and then 1 / 2 of the total amount of water (i.e., 75 parts) is added, and after stirring and soaking for 60 seconds, cement is added, and 1 / 4 of the total amount of water (i.e., 37.5 parts) is added, and then stirring and soaking is continued for 60 seconds to obtain pre-wetted aggregate.

[0116] (2) Add fly ash, silica fume, water reducer, nano-silica, organic silane coupling agent and rubber latex to the pre-wetted aggregate and stir evenly for 5 minutes.

[0117] (3) Add anti-cracking fiber to the above mixture, such as polypropylene fiber, and continue to stir evenly for 3 minutes.

[0118] (4) Finally, the remaining water (i.e. 37.5 parts) was added and stirred evenly to obtain a recycled concrete material with anti-crack function.

[0119] Comparative Example 2

[0120] The amounts of corncob residue and sodium silicate and the pretreatment step of the recycled coarse aggregate in Example 2 were removed, and the remaining raw material amounts and operating steps remained unchanged.

[0121] The preparation process is as follows:

[0122] (1) Mix the recycled coarse aggregate and the recycled fine aggregate, then add 1 / 2 of the total amount of water (i.e., 50 parts), stir and soak for 40 seconds, then add cement, add 1 / 4 of the total amount of water (i.e., 25 parts), and then continue to stir and soak for 40 seconds to obtain pre-wetted aggregate.

[0123] (2) Add fly ash, silica fume, water reducer, nano-silica, organosilane coupling agent and rubber latex to the pre-wetted aggregate. If an aminocarboxylic acid water reducer is used, stir evenly for 3 minutes.

[0124] (3) Add anti-cracking fiber to the above mixture, such as basalt fiber, and continue to stir evenly for 2 minutes.

[0125] (4) Finally, the remaining water (i.e. 25 parts) is added and stirred evenly to obtain a recycled concrete material with anti-crack function.

[0126] Comparative Example 3

[0127] The amounts of corncob residue and sodium silicate and the pretreatment step of the recycled coarse aggregate in Example 3 were removed, and the remaining raw material amounts and operating steps remained unchanged.

[0128] The preparation process is as follows:

[0129] (1) Recycled coarse aggregate and recycled fine aggregate are mixed, and then 1 / 2 of the total amount of water (i.e., 65 parts) is added, stirred and soaked for 50 seconds, and then cement is added, and 1 / 4 of the total amount of water is added, and stirred and soaked for 50 seconds to obtain pre-wetted aggregate.

[0130] (2) Add fly ash, silica fume, water reducer, nano-silica, organic silane coupling agent and rubber latex to the pre-wetted aggregate and stir evenly for 4 minutes.

[0131] (3) Add polypropylene fiber and basalt fiber in a ratio of 1:1 into the above mixture and continue stirring evenly for 2.5 minutes.

[0132] (4) Finally, the remaining water (i.e., 32.5 parts) was added and stirred evenly to obtain a recycled concrete material with anti-crack function.

[0133] Comparative Example 4

[0134] The amounts of corncob residue and sodium silicate and the pretreatment step of the recycled coarse aggregate in Example 4 were removed, and the remaining raw material amounts and operating steps remained unchanged.

[0135] The preparation process is as follows:

[0136] (1) Mix the recycled coarse aggregate and the recycled fine aggregate, then add 1 / 2 of the total amount of water (i.e. 60 parts), stir and soak for 50 seconds, then add cement, add 1 / 4 of the total amount of water, stir and soak for 50 seconds to obtain pre-wetted aggregate.

[0137] (2) Add fly ash, silica fume, water reducer, nano-silica, organic silane coupling agent and rubber latex to the pre-wetted aggregate and stir evenly for 4 minutes.

[0138] (3) Add the steel fiber into the above mixture and continue stirring for 2 minutes.

[0139] (4) Finally, the remaining water (i.e. 30 parts) is added and stirred evenly to obtain a recycled concrete material with anti-crack function.

[0140] The testing method refers to GB / T 50081-2002, and the anti-crack functional recycled concrete prepared in Examples 1-5 and Comparative Examples 1-4 is made into standard test blocks, and the compressive strength of the standard test blocks after curing for 28 days is measured. The specific test results are shown in the following 2:

[0141] According to JGJ / T 193-2009, the crack resistance performance of the test pieces of the crack-resistant functional recycled concrete prepared in Examples 1-5 and Comparative Examples 1-4 was tested, and the crack resistance grade of the crack-resistant functional recycled concrete was determined according to the scoring rules in Table 1. The specific test results are shown in Table 2 below:

[0142] Table 1 Crack resistance rating of recycled concrete with crack resistance function

[0143] <![CDATA[Total cracking area per unit area c (mm 2 / m 2 )]]> grade c≥1000 LI 700≤c<1000 L-II 400≤c<700 L-III 100≤c<400 L-IV c<100 LV

[0144] Table 2 Performance test of crack-resistant recycled concrete

[0145]

[0146]

[0147] It can be seen from Table 2 that the 28d compressive strength of the anti-crack functional recycled concrete prepared in the examples of the present application is greater than 60MPa, the 28d compressive strength is high, and the crack resistance grade is not lower than L-IV, the crack resistance is good, and all are better than the comparative example. By comparison with the comparative example, it can be clearly seen that the concrete prepared from the recycled coarse aggregate pretreated with corncob residue and sodium silicate has a good anti-crack functional effect.

[0148] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it accordingly. It cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, some simple deductions or substitutions can be made without departing from the concept of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be covered within the protection scope of the present invention.

Claims

1. A recycled concrete material with anti-crack function, characterized in that: The invention comprises, by weight, 300-400 parts of recycled coarse aggregate, 200-300 parts of recycled fine aggregate, 150-200 parts of cement, 50-80 parts of fly ash, 20-30 parts of silica fume, 3-5 parts of water reducer, 150-200 parts of corncob residue, 0.1-0.2 parts of sodium silicate, 5-10 parts of anti-cracking fiber, 5-10 parts of nano silicon dioxide, 2-5 parts of organic silane coupling agent, 8-12 parts of rubber latex and 100-150 parts of water; wherein the recycled The coarse aggregate is pretreated with corn cob residue and sodium silicate, and then mixed with the remaining raw materials. The pretreatment method comprises the following steps: continuously grinding the corn cob residue into a fluid state, and then introducing it into the recycled coarse aggregate, gradually raising the temperature to 90-120°C, and this process lasts for 11-30s. Then, sodium silicate with a concentration of 20-40mmol / L is added, and the temperature is adjusted to 70-80°C and maintained for 20-30min to obtain the pretreated recycled coarse aggregate.

2. The recycled concrete material with anti-crack function according to claim 1, characterized in that: The weight ratio of cellulose, hemicellulose and lignin in the corncob residue is 20-30:10-20:40-50.

3. The recycled concrete material with anti-crack function according to claim 1, characterized in that: The anti-cracking fiber is a combination of one or more of polypropylene fiber, basalt fiber, steel fiber and polyvinyl alcohol fiber.

4. The recycled concrete material with anti-crack function according to claim 1, characterized in that: The water reducer is one of a naphthalene-based water reducer, a polycarboxylic acid-based water reducer, an aminocarboxylic acid-based water reducer and a melamine-based water reducer.

5. The recycled concrete material with anti-crack function according to claim 1, characterized in that: The cement is slag cement and / or fly ash cement with low hydration heat.

6. The recycled concrete material with anti-crack function according to claim 1, characterized in that: The recycled coarse aggregate and recycled fine aggregate are obtained by crushing and screening waste concrete, and the particle sizes thereof are 5-25 mm and 0.15-5 mm respectively.

7. The recycled concrete material with anti-crack function according to claim 1, characterized in that: The weight ratio of the mixture of nano silicon dioxide, organic silane coupling agent and rubber latex is 2-4:1-2:3-5.

8. The recycled concrete material with anti-crack function according to claim 1, characterized in that: Calculated by weight, it includes 400 parts of recycled coarse aggregate, 200 parts of recycled fine aggregate, 150 parts of cement, 80 parts of fly ash, 20 parts of silica fume, 3 parts of water reducer, 150 parts of corn cob residue, 0.2 parts of sodium silicate, 5 parts of anti-cracking fiber, 6 parts of nano-silica, 2 parts of organic silane coupling agent, 10 parts of rubber latex and 100 parts of water.

9. A process for preparing a recycled concrete material with anti-crack function, characterized in that: The following steps are involved: (1) The corncob residue is continuously ground into a fluid state, and then introduced into the recycled coarse aggregate, and the temperature is gradually increased to 90-120°C, and this process lasts for 11-30 seconds, and then sodium silicate with a concentration of 20-40 mmol / L is added, and the temperature is adjusted to 70-80°C, and maintained for 20-30 minutes to obtain the pretreated recycled coarse aggregate; (2) mixing the pretreated recycled coarse aggregate with the recycled fine aggregate, and then adding 1 / 2 of the total amount of water, stirring and soaking for 40 to 60 seconds, adding cement, adding nano-silica, organic silane coupling agent, rubber latex and 1 / 4 of the total amount of water, and then continuing to stir and soak for 40 to 60 seconds to obtain pre-wetted aggregate; (3) Add fly ash, silica fume and water reducing agent to the pre-wetted aggregate and stir evenly for 3 to 5 minutes; (4) Add the anti-cracking fiber to the above mixture and continue to stir evenly for 2 to 3 minutes; (5) Finally, add the remaining water and stir evenly to obtain a recycled concrete material with anti-crack function.

10. The process for preparing the recycled concrete material with anti-crack function according to claim 9, characterized in that: In step (1), the corn cob residue is continuously ground into a fluid state, and then introduced into the recycled coarse aggregate, and the temperature is gradually increased to 110°C. This process lasts for 30 seconds, and then sodium silicate with a concentration of 35 mmol / L is added, and the temperature is adjusted to 80°C and maintained for 30 minutes to obtain the pretreated recycled coarse aggregate.

Citation Information

Patent Citations

  • Anti-cracking recycled concrete and preparation method thereof

    CN113735520A

  • Anti-cracking recycled concrete and preparation method thereof

    CN116477897A